Price setting behaviour in Denmark: A study of CPI Micro Data 1997-2005 - Bo William Hansen; Niels Lynggård Hansen (Danmarks Nationalbank, 2006)
This paper provides empirical evidence on the degree of price rigidity and price flexibility in Denmark. Our data relies on unpublished data from Statistics Denmark on the Danish CPI. The dataset covers the period 1997-2005 and contains around 2.7 million monthly price records. The paper reveals a substantial amount of heterogeneity in the frequency and size of price adjustments across sectors and products. Most price changes are increases, but price decreases are not uncommon. Price changes are generally sizeable compared to aggregate and sectoral inflation rates. We explore how these features are affected by e.g. seasonality, changes in indirect taxation and the level of inflation. Our evidence emphasises the importance of price stickiness and supports the existence of both time and state-dependent pricing strategies.
Keywords: 330